Body posture of children aged 7–9 - Drzał-Grabiec, Justyna; Snela, Sławomir; Bibrowicz, Karol; Szczepanowska-Wołowiec, Beata (European Journal of Clinical and Experimental Medicine, 2011)
<section id="block-views-streszczenie-block" class="block block-views clearfix" style="box-sizing: border-box; display: block; color: #666666; font-family: Lato, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Background: Human body posture is variable and also influenced by a number of factors. The aim of the study was to evaluate changes in body posture based on parameters describing body posture among children aged 7–9. Material and methods: The studies were conducted in the year 2009 in selected primary schools in Podkarpackie and Silesia Province. The total of 563 pupils aged 7-9 were examined. The subjects’ body posture was measured by means of photogrammetric method using the Moiré phenomenon; 20 parameters describing body posture were taken into consideration. Results: The results of this study revealed some tendencies in shaping physiological curvatures of spine. Parameters describing body posture change with age. Conclusions: The results of the analysis can be used for further observations of the development of body posture. In evaluation of body posture it is necessary to take into account the age of the examined children.